Solid acid catalyst as well as preparation method and application thereof

By using a solid acid catalyst with a specific composition in the reaction of toluene disproportionation and alkyl transfer, the problems of high reaction temperature and hydrogen consumption in the prior art are solved, and the catalytic effects of low temperature, low hydrogen consumption and high stability are achieved, and energy consumption and material consumption are reduced.

CN119680585AActive Publication Date: 2025-03-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202311221013.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-03-25
Estimated Expiration
2043-09-21

AI Technical Summary

Technical Problem

In the prior art, the reaction temperature and hydrogen consumption of toluene disproportionation and alkyl transfer reactions are relatively high, resulting in large energy and material consumption, which is difficult to meet the needs of cost reduction and efficiency improvement.

Method used

A solid acid catalyst is provided, including an alumina support, Group IVB and/or Group IV metal oxides, Pt metals, Group IIA metals and sulfate ions. By regulating the ratio of strong acids and medium acids in the catalyst, the acidic distribution of the catalyst is optimized and the reaction temperature and hydrogen consumption are reduced.

Benefits of technology

Low-temperature operation, low-hydrogen consumption and high stability of toluene disproportionation and alkyl transfer reaction are achieved, energy consumption and material consumption are reduced, and the stability and economicality of the catalyst are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004460589700000111
    Figure BDA0004460589700000111
  • Figure BDA0004460589700000121
    Figure BDA0004460589700000121
  • Figure BDA0004460589700000122
    Figure BDA0004460589700000122
Patent Text Reader

Abstract

The invention discloses a solid acid catalyst as well as a preparation method and application thereof. The solid acid catalyst is prepared from the following components in percentage by mass on the basis of the weight of the catalyst: a) 54 to 98 percent of an aluminum oxide carrier; b) 1%-30% of at least one metal selected from IVB group and / or IV group metals; c) 0.001% to 1% of Pt metal; d) 0.1%-5% of at least one metal selected from group IIA metals; e) 0.1% to 10% of sulfate ions; the sum of the strong acid amount and the medium strong acid amount of the catalyst accounts for more than or equal to 80% of the total acid amount of the catalyst; the amount of the strong acid accounts for less than or equal to 50% of the total acid amount of the catalyst. The catalyst is used for toluene disproportionation and transalkylation reaction, and has the characteristics of low reaction temperature, low hydrogen consumption and good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of solid catalysts, and specifically relates to a solid acid catalyst and a preparation method and application thereof. Background Art

[0002] Toluene disproportionation and transalkylation is one of the core reactions in the aromatics complex, and its product xylene is an important organic raw material. Reducing the energy and material consumption of the disproportionation and transalkylation process by improving the catalytic performance of the catalyst is an important way to reduce costs and increase efficiency in the process. The transalkylation reaction is an acid-catalyzed reaction, and regulating the acid properties of solid acids to match the reaction is a research focus of catalyst design. Solid acid catalysts are widely used in various industrial production processes, among which the solid superacid obtained after sulfation treatment is an important type of solid acid. Metal oxides can generally achieve a significant increase in acid strength after sulfation treatment. By adding additives to regulate the distribution of acid strength, the acid properties of the catalyst can be matched with the reaction.

[0003] CN113492016A discloses a two-component catalyst for toluene disproportionation and transalkylation and its preparation method. The catalyst comprises a modified needle-shaped MOR molecular sieve and a modified nano ZSM-5 molecular sieve. The modified needle-shaped MOR molecular sieve is prepared by impregnating and modifying a needle-shaped hydrogen-type MOR molecular sieve with a length-to-diameter ratio of 3 to 10:1 with an inorganic oxide; the modified nano ZSM-5 molecular sieve is prepared by impregnating and modifying a hydrogen-type nano ZSM-5 molecular sieve with a particle size of 50 to 300 nm with an inorganic oxide. The inorganic oxide is one or more of the oxides of Co, Mo, Ru, Cu, Be and W. When the catalyst is used, the reaction temperature is required to be 300 to 500°C and the hydrogen-to-hydrocarbon ratio is 10:1 to 1:1.

[0004] CN102909066A discloses a toluene disproportionation and transalkylation catalyst. The catalyst is composed of a hydrogen-type EU-1 / Beta composite molecular sieve, an inorganic refractory oxide, and a second metal component. CN102909068A discloses a toluene disproportionation and transalkylation catalyst. The catalyst is composed of a hydrogen-type EU-1 / ZSM-5 composite molecular sieve, an inorganic refractory oxide, and a second metal component.

[0005] In summary, the current research on toluene disproportionation and transalkylation catalysts is mostly focused on molecular sieve systems, and the reaction temperature and hydrogen consumption are generally high, while there are few literature reports on the use of sulfated metal oxide systems for reactions at low temperatures. Summary of the invention

[0006] In view of the problems of high reaction temperature and hydrogen consumption in toluene disproportionation and transalkylation reactions in the prior art, the present invention provides a new solid acid catalyst and its preparation method and application. The catalyst is used for toluene disproportionation and transalkylation reactions and has the characteristics of low reaction temperature, low hydrogen consumption and good stability.

[0007] The first aspect of the present invention provides a solid acid catalyst, which comprises, based on the weight of the catalyst and measured by mass fraction:

[0008] a) 54% to 98% alumina support;

[0009] b) 1% to 30% of at least one metal selected from Group IVB and / or Group IV, calculated as the corresponding metal oxide;

[0010] c) 0.001% to 1% of Pt metal;

[0011] d) 0.1% to 5% of at least one metal selected from Group IIA;

[0012] e) 0.1% to 10% sulfate ion;

[0013] The sum of the strong acid content and the medium-strong acid content of the catalyst accounts for ≥80% of the total acid content of the catalyst, preferably 80% to 99%; the strong acid content accounts for ≤50% of the total acid content of the catalyst, preferably 5% to 50%.

[0014] According to the present invention, the ratio of the sum of the strong acid content and the medium-strong acid content of the catalyst to the total acid content of the catalyst is further preferably 80% to 95%, for example, 82%, 83%, 84%, 85%, 89%, 90%, 92%, 93%, 95%, etc., and any value in the range formed by any two of these values.

[0015] According to the present invention, the ratio of the strong acid amount of the catalyst to the total acid amount of the catalyst is further preferably 20% to 50%, for example, 20%, 25%, 28%, 30%, 35%, 40%, 45%, 46%, 48%, 50%, etc., and any value in the range formed by any two of these values.

[0016] According to the present invention, preferably, the catalyst comprises:

[0017] a) 68% to 88% alumina carrier;

[0018] b) 10% to 25% of at least one metal selected from Group IVB and / or Group IV, calculated as the corresponding metal oxide;

[0019] c) 0.01% to 0.5% Pt metal;

[0020] d) 0.5% to 2% of at least one metal selected from Group IIA;

[0021] e) 1% to 5% sulfate ions.

[0022] According to the present invention, the alumina in component a) is mesoporous alumina; the pore size distribution of the alumina is 2 to 50 nm. The specific surface area of ​​the alumina is ≥350 m 2 / g, preferably 350 to 500 m 2 / g.

[0023] According to the present invention, component b) is at least one selected from Zr, Ti, and Sn, preferably Zr.

[0024] According to the present invention, component d) is at least one selected from Ca, Ba, and Mg, preferably Mg.

[0025] The second aspect of the present invention provides a method for preparing the solid acid catalyst, comprising:

[0026] (1) mixing alumina, a source of component b) and a precipitant, and then adding a source of component d) to obtain a mixture;

[0027] (2) subjecting the mixture obtained in step (1) to a first hydrothermal reaction, a second hydrothermal reaction, and a third hydrothermal reaction, and then separating to obtain a solid;

[0028] (3) subjecting the solid Pt-loaded substrate obtained in step (2) to a first calcination;

[0029] (4) treating the first calcined product obtained in step (3) with a sulfating agent, and then calcining it for a second time to obtain the catalyst.

[0030] According to the present invention, the reaction temperature of the second hydrothermal reaction is higher than that of the first hydrothermal reaction; the temperature of the third hydrothermal reaction is higher than that of the second hydrothermal reaction. Preferably, the reaction temperature of the second hydrothermal reaction is 10 to 50°C higher than that of the first hydrothermal reaction. The reaction temperature of the third hydrothermal reaction is 10 to 50°C higher than that of the second hydrothermal reaction.

[0031] According to the present invention, in step (1), the source of component b) is a metal salt containing component b), preferably a soluble metal salt. Further, the source of component b) includes at least one of nitrate, acetate, and chloride of the metal of component b), preferably acetate. The alumina is mesoporous alumina. The pore size distribution of the alumina is 2 to 50 nm. The specific surface area of ​​the alumina is ≥350 m 2 / g, preferably 350-500m 2 / g. The precipitant is at least one of urea, KOH and NaOH. The molar ratio of the component b) metal to the precipitant is 1:1 to 1:30, preferably 1:5 to 15.

[0032] According to the present invention, further, a proper amount of water can be added to the system of alumina, component b) source and precipitant, and the mass ratio of the amount of alumina added to the amount of water added is in the range of 1:0.5 to 1:50.

[0033] According to the present invention, further, in step (1), the alumina, the component b) source and the precipitant are mixed and then stirred thoroughly at a temperature of 15 to 40° C. and a stirring time of 3 to 12 hours.

[0034] According to the present invention, further, in step (1), after adding the source of component d), ultrasonic treatment is performed. The ultrasonic operation is performed in a water bath of an ultrasonic instrument. The ultrasonic frequency is 20 to 150 kHz, the ultrasonic temperature is 15 to 40° C., and the ultrasonic time is 1 to 5 hours.

[0035] According to the present invention, in step (2), the device for the hydrothermal reaction is a hydrothermal kettle. The temperature of the first hydrothermal reaction is 120-150°C and the time is 2-20h; the temperature of the second hydrothermal reaction is 150-170°C and the time is 2-20h. The temperature of the third hydrothermal reaction is 170-200°C and the time is 2-20h. The reaction times of the first hydrothermal reaction, the second hydrothermal reaction and the third hydrothermal reaction can be the same or different.

[0036] According to the present invention, in step (2), the solid obtained after separation can be washed and / or dried. The washing can be carried out by at least one of ethanol and deionized water. The drying temperature is 60 to 120° C. and the drying time is 2 to 20 hours.

[0037] According to the present invention, the method of loading Pt in step (3) can be an impregnation method. That is, the solid obtained in step (2) is impregnated in a Pt source solution. The Pt source is at least one of chloroplatinic acid and platinum chloride. The impregnation temperature is 15 to 40°C and the time is 2 to 20 hours. Drying can be performed after impregnation. The drying temperature is 60 to 120°C and the time is 2 to 20 hours. The atmosphere of the first calcination is an oxygen atmosphere, preferably air. The temperature of the first calcination is 300 to 500°C and the time is 2 to 20 hours.

[0038] According to the present invention, in step (4), the sulfating agent is at least one of sulfuric acid, ammonium sulfate, and ammonium bisulfate. The sulfating agent exists in the form of a solution. The concentration of the sulfating agent solution is 0.1 to 3 mol / L, preferably 0.5 to 1.5 mol / L. The mass of the first roasting product and the volume of the sulfating agent satisfy the following relationship: 1 g / 10 mL to 1 g / 200 mL. The sulfating agent treatment method is soaking, preferably soaking under stirring. The temperature of the sulfating treatment is 15 to 40°C, and the time is 2 to 20 hours. Drying can be performed after the sulfating treatment. The drying temperature is 60 to 120°C, and the drying time is 2 to 20 hours.

[0039] According to the present invention, in step (4), the atmosphere of the second calcination is an oxygen atmosphere, preferably air. The temperature of the second calcination is 300-650° C., and the time is 2-20 hours.

[0040] The third aspect of the present invention provides the use of the solid acid catalyst or the solid acid catalyst prepared by the above method in toluene disproportionation and transalkylation reactions.

[0041] According to the present invention, the reaction conditions of the application are: reaction temperature is 100-500°C, preferably 100-300°C, more preferably below 300°C, reaction pressure is 1.0-8.0MPa, hydrogen-to-hydrocarbon molar ratio is 0.1-10, preferably 0.1-5, liquid raw material weight space velocity is 0.5-10h -1 .

[0042] Compared with the prior art, the present invention has the following advantages:

[0043] 1. The solid acid catalyst of the present invention comprises: a) 54% to 98% of an alumina carrier; b) 1% to 30% of at least one metal selected from Group IVB and / or Group IV; c) 0.001% to 1% of a Pt metal; d) 0.1% to 5% of at least one metal selected from Group IIA; e) 0.1% to 10% of a sulfate ion; the sum of the strong acid content and the medium-strong acid content of the catalyst accounts for ≥80% of the total acid content of the catalyst; the proportion of the strong acid content to the total acid content of the catalyst is ≤50%. The inventor of the present invention has found through research that in the toluene disproportionation and transalkylation reactions, the strong B acid site is conducive to the transfer of active protons on the catalyst surface, but is more easily deactivated, while the medium-strong acid site can simultaneously ensure the conversion rate and stability of the reaction. Therefore, by regulating the ratio of these two acid sites in the catalyst, the catalyst stability can be effectively improved. The sulfate ions and metal oxides of group IVB and / or group IV dispersed in the pore structure of the mesoporous material of the present invention have higher acid strength and acid density, and can realize the alkyl transfer reaction at a lower temperature.

[0044] 2. In the preparation method provided by the present invention, mesoporous alumina is used as a carrier, and a precipitation method is used to introduce Group IVB and / or Group IV metals and Group IIA metals, and three hydrothermal reactions are carried out in sequence, and then Pt metal is loaded and treated with a sulfating agent to prepare the catalyst. The preparation method of the present invention is simple to operate, economically feasible, and easy to industrially apply. The method uses three hydrothermal methods, and further preferably adds Lewis alkaline metal oxides as additives to the raw materials. The prepared catalyst has an appropriate acid distribution, and the catalyst stability can be effectively improved by regulating the ratio of strong acid and medium-strong acid in the catalyst.

[0045] 3. In the prior art, the reaction temperature of toluene disproportionation and transalkylation reaction is generally required to be relatively high, usually at 300-500°C. The solid acid catalyst provided by the present invention is used for toluene disproportionation and transalkylation reaction, and has the characteristics of low reaction temperature, low hydrogen consumption and good stability. Further preferably, the solid acid catalyst provided by the present invention is suitable for toluene disproportionation and transalkylation reaction at a temperature below 300°C. DETAILED DESCRIPTION

[0046] The technical solution of the present invention is further described below in conjunction with embodiments, but is not limited to the following embodiments.

[0047] In the present invention, the 3Flex-Physisorption fully automatic specific surface area and pore size distribution analyzer produced by Micromeritics, USA, was used to analyze the N 2 Isothermal adsorption-desorption characterization, the adsorbate is high-purity N 2 The adsorption temperature was -196 °C. Before testing, the sample was vacuum-treated at 350 °C for 3 h to remove the adsorbed impurities. The specific surface area was calculated using the BET method, and the pore structure characteristics were analyzed using the BJH method.

[0048] In the present invention, the acidity and acidity of the sample are determined by using the Nexsus TM infrared spectrometer (Py-IR) of Nicolet Company of the United States. During the test, the sample is pressed into a tablet and evacuated to 10 -4 Pa, heat treatment at 400℃ for 2h, static adsorption of pyridine for 1min after the temperature dropped to 200℃, equilibrated for 5min, low vacuum pumping for 10min, high vacuum pumping for 30min, and then gradually heating the sample cell to collect Py-IR patterns of the samples at 200℃, 300℃ and 400℃, respectively, where the amount of strong acid is measured by the amount of acid after desorption at 400℃, the amount of medium-strong acid is measured by the amount of acid after desorption at 300℃ minus the amount of acid after desorption at 400℃, the amount of weak acid is measured by the amount of acid after desorption at 200℃ minus the amount of acid after desorption at 300℃, and the total acid amount is the sum of the weak acid, medium-strong acid and strong acid.

[0049] In the present invention, % refers to mass percentage unless otherwise specified.

[0050] [Example 1]

[0051] (1) Mesoporous alumina (specific surface area 390 m 2 / g), mixed with zirconium nitrate and urea in deionized water and stirred thoroughly at 30°C for 10 hours. The mesoporous alumina is 71.2% of the total weight of the catalyst, and the weight percentage of Zr (in terms of ZrO 2 The molar ratio of Zr to urea is 1:10, and the mass ratio of alumina to deionized water is 1:10 to obtain a mixture A1.

[0052] A magnesium acetate solution was added to the mixture A1, wherein the weight percentage of Mg was 1.5% of the total weight of the catalyst, and ultrasonicated at 50 kHz at 30° C. for 3 h in an ultrasonic machine to obtain a mixture A2.

[0053] (2) The mixture A2 was transferred into a hydrothermal reactor and subjected to hydrothermal reaction at 140° C., 160° C. and 190° C. for 15 h, respectively. After washing with deionized water, the mixture was dried at 90° C. for 12 h to obtain a solid powder A3.

[0054] (3) Using chloroplatinic acid as a precursor, Pt (weight percentage is 0.3% of the total weight of the catalyst) is impregnated on the solid powder A3, dried at 90°C for 12 hours, and then calcined at 450°C for 10 hours to obtain solid powder A4.

[0055] (4) The solid powder A4 was subjected to sulfation treatment at a ratio of 1 g / 50 mL of the solid powder and a sulfation reagent. 1 mol / L of dilute sulfuric acid was used as the sulfation reagent. The solid powder was stirred at 30°C for 10 h, dried at 90°C for 10 h, and calcined at 600°C for 5 h to obtain catalyst C1.

[0056] The catalyst composition and acid properties are shown in Table 1.

[0057] The evaluation conditions of the catalyst are as follows: 5 g of catalyst C1 is weighed and loaded into a fixed bed reactor, 70 mL / min of hydrogen is introduced, the temperature is maintained at 450°C for 2 hours at a pressure of 4 MPa, the temperature is lowered to 290°C, the hydrogen-to-hydrocarbon molar ratio is adjusted to 0.5, and after the temperature stabilizes, the reaction raw materials toluene and 1,2,4-trimethylbenzene (mass ratio of 1:1) are introduced for reaction for 20 hours. The reaction results are shown in Table 1.

[0058] [Example 2]

[0059] (1) Mesoporous alumina (specific surface area 390 m 2 / g), mixed with zirconium nitrate and urea in deionized water and stirred thoroughly at 30°C for 10 hours. The mesoporous alumina is 84.2% of the total weight of the catalyst, and the weight percentage of Zr (in terms of ZrO 2 The molar ratio of Zr to urea is 1:10, and the mass ratio of alumina to deionized water is 1:10 to obtain a mixture A1.

[0060] A magnesium acetate solution was added to the mixture A1, wherein the weight percentage of Mg was 1.5% of the total weight of the catalyst, and ultrasonicated at 50 kHz at 30° C. for 3 h in an ultrasonic machine to obtain a mixture A2.

[0061] (2) The mixture A2 was transferred into a hydrothermal reactor and subjected to hydrothermal reaction at 140, 160 and 190° C. for 15 h, respectively. After washing with deionized water, it was dried at 90° C. for 12 h to obtain a solid powder A3.

[0062] (3) Using chloroplatinic acid as a precursor, Pt (weight percentage is 0.3% of the total weight of the catalyst) is impregnated on the solid powder A3, dried at 90°C for 12 hours, and then calcined at 450°C for 10 hours to obtain solid powder A4.

[0063] (4) Solid powder A4 was subjected to sulfation treatment at a ratio of 1 g / 50 mL of a sulfation reagent. 1 mol / L of dilute sulfuric acid was used as a sulfation reagent. The solid powder was stirred at 30°C for 10 h, dried at 90°C for 10 h, and calcined at 600°C for 5 h to obtain catalyst C1.

[0064] The evaluation conditions of the catalyst are as follows: 5 g of catalyst C1 is weighed and loaded into a fixed bed reactor, 70 mL / min of hydrogen is introduced, the temperature is maintained at 450°C for 2 hours at a pressure of 4 Ma, the temperature is lowered to 290°C, the hydrogen-to-hydrocarbon molar ratio is adjusted to 0.5, and after the temperature stabilizes, the reaction raw materials toluene and 1,2,4-trimethylbenzene (mass ratio of 1:1) are introduced for reaction for 20 hours. The reaction results are shown in Table 1.

[0065] [Example 3]

[0066] (1) Mesoporous alumina (specific surface area 390 m 2 / g), mixed with tetrabutyl titanate and urea in deionized water and stirred thoroughly at 30°C for 10 hours. The mesoporous alumina is 71.4% of the total weight of the catalyst, and the weight percentage of Ti (in terms of TiO 2 The molar ratio of Ti to urea is 1:10, and the mass ratio of alumina to deionized water is 1:10 to obtain a mixture A1.

[0067] A magnesium acetate solution was added to the mixture A1, wherein the weight percentage of Mg was 1.5% of the total weight of the catalyst, and ultrasonicated at 50 kHz at 30° C. for 3 h in an ultrasonic machine to obtain a mixture A2.

[0068] (2) The mixture A2 was transferred into a hydrothermal reactor and subjected to hydrothermal reaction at 140, 160 and 190° C. for 15 h, respectively. After washing with deionized water, it was dried at 90° C. for 12 h to obtain a solid powder A3.

[0069] (3) Using chloroplatinic acid as a precursor, Pt (weight percentage is 0.3% of the total weight of the catalyst) is impregnated on the solid powder A3, dried at 90°C for 12 hours, and then calcined at 450°C for 10 hours to obtain solid powder A4.

[0070] (4) Solid powder A4 was subjected to sulfation treatment at a ratio of 1 g / 50 mL of a sulfation reagent. 1 mol / L of dilute sulfuric acid was used as a sulfation reagent. The solid powder was stirred at 30°C for 10 h, dried at 90°C for 10 h, and calcined at 600°C for 5 h to obtain catalyst C1.

[0071] The evaluation conditions of the catalyst are as follows: 5 g of catalyst C1 is weighed and loaded into a fixed bed reactor, 70 mL / min of hydrogen is introduced, the temperature is maintained at 450°C for 2 hours at a pressure of 4 Ma, the temperature is lowered to 290°C, the hydrogen-to-hydrocarbon molar ratio is adjusted to 0.5, and after the temperature stabilizes, the reaction raw materials toluene and 1,2,4-trimethylbenzene (mass ratio of 1:1) are introduced for reaction for 20 hours. The reaction results are shown in Table 1.

[0072] [Example 4]

[0073] (1) Mesoporous alumina (specific surface area 390 m 2 / g), mixed with zirconium nitrate and urea in deionized water and stirred thoroughly at 30°C for 10 hours. The mesoporous alumina is 71.2% of the total weight of the catalyst, and the weight percentage of Zr (in terms of ZrO 2 The molar ratio of Zr to urea is 1:10, and the mass ratio of alumina to deionized water is 1:10 to obtain a mixture A1.

[0074] Calcium acetate solution was added to mixture A1, wherein the weight percentage of Ca was 1.5% of the total weight of the catalyst, and ultrasonicated at 50 kHz and 30° C. for 3 h in an ultrasonic machine to obtain mixture A2.

[0075] (2) The mixture A2 was transferred into a hydrothermal reactor and subjected to hydrothermal reaction at 140, 160 and 190° C. for 15 h, respectively. After washing with deionized water, it was dried at 90° C. for 12 h to obtain a solid powder A3.

[0076] (3) Using chloroplatinic acid as a precursor, Pt (weight percentage is 0.3% of the total weight of the catalyst) is impregnated on the solid powder A3, dried at 90°C for 12 hours, and then calcined at 450°C for 10 hours to obtain solid powder A4.

[0077] (4) Solid powder A4 was subjected to sulfation treatment at a ratio of 1 g / 50 mL of a sulfation reagent. 1 mol / L of dilute sulfuric acid was used as a sulfation reagent. The solid powder was stirred at 30°C for 10 h, dried at 90°C for 10 h, and calcined at 600°C for 5 h to obtain catalyst C1.

[0078] The evaluation conditions of the catalyst are as follows: 5 g of catalyst C1 is weighed and loaded into a fixed bed reactor, 70 mL / min of hydrogen is introduced, the temperature is maintained at 450°C for 2 hours at a pressure of 4 Ma, the temperature is lowered to 290°C, the hydrogen-to-hydrocarbon molar ratio is adjusted to 0.5, and after the temperature stabilizes, the reaction raw materials toluene and 1,2,4-trimethylbenzene (mass ratio of 1:1) are introduced for reaction for 20 hours. The reaction results are shown in Table 1.

[0079] [Example 5]

[0080] (1) Mesoporous alumina (specific surface area 390 m 2 / g), mixed with zirconium nitrate and urea in deionized water and stirred thoroughly at 30°C for 10 hours. The mesoporous alumina is 72.2% of the total weight of the catalyst, and the weight percentage of Zr (in terms of ZrO 2 The molar ratio of Zr to urea is 1:10, and the mass ratio of alumina to deionized water is 1:10 to obtain a mixture A1.

[0081] A magnesium acetate solution was added to the mixture A1, wherein the weight percentage of Mg was 0.5% of the total weight of the catalyst, and ultrasonicated at 50 kHz at 30° C. for 3 h in an ultrasonic machine to obtain a mixture A2.

[0082] (2) The mixture A2 was transferred into a hydrothermal reactor and subjected to hydrothermal reaction at 140, 160 and 190° C. for 15 h, respectively. After washing with deionized water, it was dried at 90° C. for 12 h to obtain a solid powder A3.

[0083] (3) Using chloroplatinic acid as a precursor, Pt (weight percentage is 0.3% of the total weight of the catalyst) is impregnated on the solid powder A3, dried at 90°C for 12 hours, and then calcined at 450°C for 10 hours to obtain solid powder A4.

[0084] (4) Solid powder A4 was subjected to sulfation treatment at a ratio of 1 g / 50 mL of a sulfation reagent. 1 mol / L of dilute sulfuric acid was used as a sulfation reagent. The solid powder was stirred at 30°C for 10 h, dried at 90°C for 10 h, and calcined at 600°C for 5 h to obtain catalyst C1.

[0085] The evaluation conditions of the catalyst are as follows: 5 g of catalyst C1 is weighed and loaded into a fixed bed reactor, 70 mL / min of hydrogen is introduced, the temperature is maintained at 450°C for 2 hours at a pressure of 4 Ma, the temperature is lowered to 290°C, the hydrogen-to-hydrocarbon molar ratio is adjusted to 0.5, and after the temperature stabilizes, the reaction raw materials toluene and 1,2,4-trimethylbenzene (mass ratio of 1:1) are introduced for reaction for 20 hours. The reaction results are shown in Table 1.

[0086] [Example 6]

[0087] (1) Mesoporous alumina (specific surface area 390 m 2 / g), mixed with zirconium nitrate and urea in deionized water and stirred thoroughly at 30°C for 10 hours. The mesoporous alumina is 71.2% of the total weight of the catalyst, and the weight percentage of Zr (in terms of ZrO 2 The molar ratio of Zr to urea is 1:10, and the mass ratio of alumina to deionized water is 1:10 to obtain a mixture A1.

[0088] A magnesium acetate solution was added to the mixture A1, wherein the weight percentage of Mg was 1.5% of the total weight of the catalyst, and ultrasonicated at 50 kHz at 30° C. for 3 h in an ultrasonic machine to obtain a mixture A2.

[0089] (2) The mixture A2 was transferred into a hydrothermal reactor and subjected to hydrothermal reaction at 140, 160 and 190° C. for 8 h, respectively. After washing with deionized water, the mixture was dried at 90° C. for 12 h to obtain a solid powder A3.

[0090] (3) Using chloroplatinic acid as a precursor, Pt (weight percentage is 0.3% of the total weight of the catalyst) is impregnated on the solid powder A3, dried at 90°C for 12 hours, and then calcined at 450°C for 10 hours to obtain solid powder A4.

[0091] (4) Solid powder A4 was subjected to sulfation treatment at a ratio of 1 g / 50 mL of a sulfation reagent. 1 mol / L of dilute sulfuric acid was used as a sulfation reagent. The solid powder was stirred at 30°C for 10 h, dried at 90°C for 10 h, and calcined at 600°C for 5 h to obtain catalyst C1.

[0092] The evaluation conditions of the catalyst are as follows: 5 g of catalyst C1 is weighed and loaded into a fixed bed reactor, 70 mL / min of hydrogen is introduced, the temperature is maintained at 450°C for 2 hours at a pressure of 4 Ma, the temperature is lowered to 290°C, the hydrogen-to-hydrocarbon molar ratio is adjusted to 0.5, and after the temperature stabilizes, the reaction raw materials toluene and 1,2,4-trimethylbenzene (mass ratio of 1:1) are introduced for reaction for 20 hours. The reaction results are shown in Table 1.

[0093] [Example 7]

[0094] (1) Mesoporous alumina (specific surface area 390 m 2 / g), mixed with zirconium nitrate and urea in deionized water and stirred thoroughly at 30°C for 10 hours. The mesoporous alumina is 71.2% of the total weight of the catalyst, and the weight percentage of Zr (in terms of ZrO 2 The molar ratio of Zr to urea is 1:10, and the mass ratio of alumina to deionized water is 1:10 to obtain a mixture A1.

[0095] A magnesium acetate solution was added to the mixture A1, wherein the weight percentage of Mg was 1.5% of the total weight of the catalyst, and ultrasonicated at 50 kHz at 30° C. for 3 h in an ultrasonic machine to obtain a mixture A2.

[0096] (2) The mixture A2 was transferred into a hydrothermal reactor and subjected to hydrothermal reaction at 130, 150 and 170° C. for 15 h, respectively. After washing with deionized water, it was dried at 90° C. for 12 h to obtain a solid powder A3.

[0097] (3) Using chloroplatinic acid as a precursor, Pt (weight percentage is 0.3% of the total weight of the catalyst) is impregnated on the solid powder A3, dried at 90°C for 12 hours, and then calcined at 450°C for 10 hours to obtain solid powder A4.

[0098] (4) Solid powder A4 was subjected to sulfation treatment at a ratio of 1 g / 50 mL of a sulfation reagent. 1 mol / L of dilute sulfuric acid was used as a sulfation reagent. The solid powder was stirred at 30°C for 10 h, dried at 90°C for 10 h, and calcined at 600°C for 5 h to obtain catalyst C1.

[0099] The evaluation conditions of the catalyst are as follows: 5 g of catalyst C1 is weighed and loaded into a fixed bed reactor, 70 mL / min of hydrogen is introduced, the temperature is maintained at 450°C for 2 hours at a pressure of 4 Ma, the temperature is lowered to 290°C, the hydrogen-to-hydrocarbon molar ratio is adjusted to 0.5, and after the temperature stabilizes, the reaction raw materials toluene and 1,2,4-trimethylbenzene (mass ratio of 1:1) are introduced for reaction for 20 hours. The reaction results are shown in Table 1.

[0100] [Example 8]

[0101] (1) Mesoporous alumina (specific surface area 390 m 2 / g), mixed with zirconium nitrate and urea in deionized water and stirred thoroughly at 30°C for 10 hours. The mesoporous alumina is 71.5% of the total weight of the catalyst, and the weight percentage of Zr (in terms of ZrO 2 The molar ratio of Zr to urea is 1:10, and the mass ratio of alumina to deionized water is 1:10 to obtain a mixture A1.

[0102] A magnesium acetate solution was added to the mixture A1, wherein the weight percentage of Mg was 1.5% of the total weight of the catalyst, and ultrasonicated at 50 kHz at 30° C. for 3 h in an ultrasonic machine to obtain a mixture A2.

[0103] (2) The mixture A2 was transferred into a hydrothermal reactor and subjected to hydrothermal reaction at 140, 160 and 190° C. for 15 h, respectively. After washing with deionized water, it was dried at 90° C. for 12 h to obtain a solid powder A3.

[0104] (3) Using chloroplatinic acid as a precursor, Pt (weight percentage is 0.05% of the total weight of the catalyst) is impregnated on the solid powder A3, dried at 90°C for 12 hours, and then calcined at 450°C for 10 hours to obtain solid powder A4.

[0105] (4) Solid powder A4 was subjected to sulfation treatment at a ratio of 1 g / 50 mL of a sulfation reagent. 1 mol / L of dilute sulfuric acid was used as a sulfation reagent. The solid powder was stirred at 30°C for 10 h, dried at 90°C for 10 h, and calcined at 600°C for 5 h to obtain catalyst C1.

[0106] The evaluation conditions of the catalyst are as follows: 5 g of catalyst C1 is weighed and loaded into a fixed bed reactor, 70 mL / min of hydrogen is introduced, the temperature is maintained at 450°C for 2 hours at a pressure of 4 Ma, the temperature is lowered to 290°C, the hydrogen-to-hydrocarbon molar ratio is adjusted to 0.5, and after the temperature stabilizes, the reaction raw materials toluene and 1,2,4-trimethylbenzene (mass ratio of 1:1) are introduced for reaction for 20 hours. The reaction results are shown in Table 1.

[0107] [Comparative Example 1]

[0108] (1) Alumina (specific surface area 120m 2 / g), mixed with zirconium nitrate and urea in deionized water and stirred thoroughly at 30°C for 10 hours. Alumina is 72.7% of the total weight of the catalyst, and the weight percentage of Zr (in terms of ZrO 2 The molar ratio of Zr to urea is 1:10, and the mass ratio of alumina to deionized water is 1:10 to obtain a mixture A1.

[0109] A magnesium acetate solution was added to the mixture A1, wherein the weight percentage of Mg was 1.5% of the total weight of the catalyst, and ultrasonicated at 50 kHz at 30° C. for 3 h in an ultrasonic machine to obtain a mixture A2.

[0110] (2) The mixture A2 was transferred into a hydrothermal reactor and subjected to hydrothermal reaction at 140, 160 and 190° C. for 15 h, respectively. After washing with deionized water, it was dried at 90° C. for 12 h to obtain a solid powder A3.

[0111] (3) Using chloroplatinic acid as a precursor, Pt (weight percentage is 0.3% of the total weight of the catalyst) is impregnated on the solid powder A3, dried at 90°C for 12 hours, and then calcined at 450°C for 10 hours to obtain solid powder A4.

[0112] (4) Solid powder A4 was subjected to sulfation treatment at a ratio of 1 g / 50 mL of a sulfation reagent. 1 mol / L of dilute sulfuric acid was used as a sulfation reagent. The solid powder was stirred at 30°C for 10 h, dried at 90°C for 10 h, and calcined at 600°C for 5 h to obtain catalyst C1.

[0113] The catalyst composition is shown in Table 1.

[0114] The evaluation conditions of the catalyst are as follows: 5 g of catalyst C1 is weighed and loaded into a fixed bed reactor, 70 mL / min of hydrogen is introduced, the temperature is maintained at 450°C for 2 hours at a pressure of 4 Ma, the temperature is lowered to 290°C, the hydrogen-to-hydrocarbon molar ratio is adjusted to 0.5, and after the temperature stabilizes, the reaction raw materials toluene and 1,2,4-trimethylbenzene (mass ratio of 1:1) are introduced for reaction for 20 hours. The reaction results are shown in Table 1.

[0115] [Comparative Example 2]

[0116] (1) Mesoporous alumina (same as in Example 1), zirconium oxynitrate and urea were mixed in deionized water and stirred thoroughly at 30°C for 10 hours. The mesoporous alumina accounted for 71.2% of the total weight of the catalyst, and the weight percentage of Zr (in terms of ZrO 2 The molar ratio of Zr to urea is 1:10, and the mass ratio of alumina to deionized water is 1:10 to obtain a mixture A1.

[0117] A magnesium acetate solution was added to the mixture A1, wherein the weight percentage of Mg was 1.5% of the total weight of the catalyst, and ultrasonicated at 50 kHz at 30° C. for 3 h in an ultrasonic machine to obtain a mixture A2.

[0118] (2) The mixture A2 was transferred into a hydrothermal reactor and subjected to hydrothermal reaction at 150° C. for 48 h. After being washed with deionized water, it was dried at 90° C. for 12 h to obtain a solid powder A3.

[0119] (3) Using chloroplatinic acid as a precursor, Pt (weight percentage is 0.3% of the total weight of the catalyst) is impregnated on the solid powder A3, dried at 90°C for 12 hours, and then calcined at 450°C for 10 hours to obtain solid powder A4.

[0120] (4) Solid powder A4 was subjected to sulfation treatment at a ratio of 1 g / 50 mL of a sulfation reagent. 1 mol / L of dilute sulfuric acid was used as a sulfation reagent. The solid powder was stirred at 30°C for 10 h, dried at 90°C for 10 h, and calcined at 600°C for 5 h to obtain catalyst C1.

[0121] The catalyst composition is shown in Table 1.

[0122] The evaluation conditions of the catalyst are as follows: 5 g of catalyst C1 is weighed and loaded into a fixed bed reactor, 70 mL / min of hydrogen is introduced, the temperature is maintained at 450°C for 2 hours at a pressure of 4 Ma, the temperature is lowered to 290°C, the hydrogen-to-hydrocarbon molar ratio is adjusted to 0.5, and after the temperature stabilizes, the reaction raw materials toluene and 1,2,4-trimethylbenzene (mass ratio of 1:1) are introduced for reaction for 20 hours. The reaction results are shown in Table 1.

[0123] [Comparative Example 3]

[0124] (1) Mesoporous alumina (same as in Example 1), zirconium oxynitrate and urea were mixed in deionized water and stirred thoroughly at 30°C for 10 hours. The mesoporous alumina accounted for 73.2% of the total weight of the catalyst, and the weight percentage of Zr (in terms of ZrO 2 The molar ratio of Zr to urea is 1:10, and the mass ratio of alumina to deionized water is 1:10 to obtain a mixture A1.

[0125] A magnesium acetate solution was added to the mixture A1, wherein the weight percentage of Mg was 1.5% of the total weight of the catalyst, and ultrasonicated at 50 kHz at 30° C. for 3 h in an ultrasonic machine to obtain a mixture A2.

[0126] (2) The mixture A2 was transferred into a hydrothermal reactor and subjected to hydrothermal reaction at 140, 160 and 190° C. for 15 h, respectively. After washing with deionized water, it was dried at 90° C. for 12 h to obtain a solid powder A3.

[0127] (3) Using chloroplatinic acid as a precursor, Pt (weight percentage is 0.3% of the total weight of the catalyst) is impregnated on the solid powder A3, dried at 90°C for 12 hours, and then calcined at 450°C for 10 hours to obtain the catalyst.

[0128] The catalyst composition is shown in Table 1.

[0129] The evaluation conditions of the catalyst are as follows: 5 g of catalyst C1 is weighed and loaded into a fixed bed reactor, 70 mL / min of hydrogen is introduced, the temperature is maintained at 450°C for 2 hours at a pressure of 4 Ma, the temperature is lowered to 290°C, the hydrogen-to-hydrocarbon molar ratio is adjusted to 0.5, and after the temperature stabilizes, the reaction raw materials toluene and 1,2,4-trimethylbenzene (mass ratio of 1:1) are introduced for reaction for 20 hours. The reaction results are shown in Table 1.

[0130] Table 1 Preparation and composition of each catalyst

[0131]

[0132]

[0133] Note: * The content of component b) is calculated based on the metal oxide corresponding to the metal, such as Zr corresponding to ZrO 2 , Ti corresponds to TiO 2 .

[0134] **Multiple hydrothermal conditions for the same catalyst are performed in order from top to bottom.

[0135] Table 2 Catalyst acid properties and evaluation results of each example

[0136]

[0137]

[0138] Note: *** is the ratio of the sum of the strong acid content and the medium-strong acid content of the catalyst to the total acid content of the catalyst.

[0139] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A solid acid catalyst, based on the weight of the catalyst and measured by mass fraction, the solid acid catalyst comprises: a) 54% to 98% alumina support; b) 1% to 30% of at least one metal selected from Group IVB and / or Group IV, calculated as the corresponding metal oxide; c) 0.001% to 1% of Pt metal; d) 0.1% to 5% of at least one metal selected from Group IIA; e) 0.1% to 10% sulfate ion; The sum of the strong acid content and the medium-strong acid content of the catalyst accounts for ≥80% of the total acid content of the catalyst; the strong acid content accounts for ≤50% of the total acid content of the catalyst.

2. The catalyst according to claim 1, characterized in that The sum of the strong acid content and the medium-strong acid content of the catalyst accounts for 80% to 99% of the total acid content of the catalyst; the strong acid content accounts for 5% to 50% of the total acid content of the catalyst.

3. The catalyst according to claim 1, characterized in that Component a) The alumina is mesoporous alumina; preferably, the pore size distribution of the alumina is 2 to 50 nm.

4. The catalyst according to claim 1, characterized in that Component b) is at least one selected from Zr, Ti, Sn, preferably Zr; and / or component d) is at least one selected from Ca, Ba, Mg, preferably Mg.

5. A method for preparing the catalyst according to any one of claims 1 to 4, comprising: (1) mixing alumina, a source of component b) and a precipitant, and then adding a source of component d) to obtain a mixture; (2) subjecting the mixture obtained in step (1) to a first hydrothermal reaction, a second hydrothermal reaction, and a third hydrothermal reaction, and then separating to obtain a solid; (3) subjecting the solid Pt-loaded substrate obtained in step (2) to a first calcination; (4) treating the first calcined product obtained in step (3) with a sulfating agent, and then performing a second calcination to obtain the catalyst; In step (2), the reaction temperature of the second hydrothermal reaction is higher than that of the first hydrothermal reaction; and the temperature of the third hydrothermal reaction is higher than that of the second hydrothermal reaction.

6. The preparation method according to claim 5, characterized in that: In step (2), the reaction temperature of the second hydrothermal reaction is 10 to 50° C. higher than the reaction temperature of the first hydrothermal reaction; and the reaction temperature of the third hydrothermal reaction is 10 to 50° C. higher than the reaction temperature of the second hydrothermal reaction.

7. The preparation method according to claim 5, characterized in that: In step (2), the temperature of the first hydrothermal reaction is 120-150° C., and the time is 2-20 h; and / or, the temperature of the second hydrothermal reaction is 150-170° C., and the time is 2-20 h; and / or, the temperature of the third hydrothermal reaction is 170-200° C., and the time is 2-20 h.

8. The preparation method according to claim 5, characterized in that: In step (1), the source of component b) is a metal salt containing component b), preferably a soluble metal salt; further, the source of component b) includes at least one of nitrate, acetate, and chloride of the metal of component b), preferably acetate; And / or, the alumina is mesoporous alumina; the pore size of the alumina is distributed in the range of 2 to 50 nm; the specific surface area of ​​the alumina is ≥350 m 2 / g, preferably 350-500m 2 / g; And / or, the precipitant is at least one of urea, KOH, and NaOH; And / or, the molar ratio of the component b) metal to the precipitant is 1:1 to 1:

30.

9. The preparation method according to claim 5, characterized in that: In step (3), the first calcination atmosphere is an oxygen atmosphere, preferably air; the first calcination temperature is 300-500° C., and the time is 2-20 hours.

10. The preparation method according to claim 5, characterized in that: In step (4), the sulfating agent is at least one of sulfuric acid, ammonium sulfate, and ammonium bisulfate; the sulfating agent is in the form of a solution; and the concentration of the sulfating agent solution is 0.1 to 3 mol / L.

11. The preparation method according to claim 5, characterized in that: In step (4), the atmosphere of the second calcination is an oxygen atmosphere, preferably air; the temperature of the second calcination is 300 to 650° C., and the time is 2 to 20 hours.

12. Use of the catalyst according to any one of claims 1 to 4 or the solid acid catalyst prepared by the preparation method according to any one of claims 5 to 11 in toluene disproportionation and transalkylation reactions.

13. The use according to claim 12, characterized in that: The reaction conditions of the application are: reaction temperature of 100-500°C, preferably below 300°C, reaction pressure of 1.0-8.0 MPa, hydrogen-to-hydrocarbon molar ratio of 0.1-10, liquid raw material weight space velocity of 0.5-10 h -1 .

Citation Information

Patent Citations

  • Catalyst of toluene disproportionation and alkyl transference, and preparation method and application thereof

    CN102909066A

  • Catalyst of toluene disproportionation and alkyl transference, and preparation method and application thereof

    CN102909068A

  • Toluene disproportionation and transalkylation two-component catalyst and preparation method thereof

    CN113492016A

  • Solid super acidic catalyst and preparation method thereof

    CN101890355A

  • Catalyst as well as preparation method and application thereof

    CN114618569A